Celebrating Poetic Nonfiction Picture Books in Classrooms. (March 2017) - Kesler, Ted
Abstract: Children's literature plays an essential role in the literacy development of children. This department column focuses on the teaching and use of children's literature and provides educators with information about a wide range of books across multiple genres that are representative of the diverse world in which we live. A strong emphasis is placed on the importance of having diverse library collections that take into account numerous factors, such as race, class, disability, and religion. This column also offers innovative approaches for bringing children and books together, as well as content analyses and rich descriptions of titles that share common features (e.g., endpapers, the blending of poetry and nonfiction).